Tingkat Efisiensi Dan Keuntungan Usahatani Stroberi Di Desa Pancasari Kecamatan Sukasada Kabupaten Buleleng - Daniel Sariman; Cening Kardi; Nyoman Yudiarini (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2021)
ABSTRACT The purpose of this study was to analyze the production costs and revenues of strawberry farming and to analyze the profit and efficiency level of strawberry farming in Pancasari Village, Sukasada District, Buleleng Regency. The analytical method used in this study was descriptive and quantitative analysis. The sampling method used the slovin method, namely the sampling of 26 farmers. The result of this research is that the annual production cost of Strawberry farming in Pancasari Village is IDR 22,623,500.00 per land area of 29 acres or IDR 78.012 million per hectare, with annual farming income of IDR 64,044,000.00 per 29 acres or IDR 220. 841,300.00 per hectare. The profit of Strawberry farming in Pancasari Village per year is Rp. 41,420,500.00 per land area of 29 acres, or Rp. 142,829,300.00 per hectare, with farming efficiency or R/C Ratio of 2.83